Haemorrhage post biopsy of a bronchial carcinoid - Vadivelu, Sangeta; Abdul Rahaman, Jamalul Azizi; Kho, Sze Shyang; Wong, Soo Fen; Nasaruddin, Mona Zaria (The Interventionalist Journal, 2022)
Background: Bronchial carcinoid tumours are rare, indolent, malignant neuroendocrine tumours derived from Kulchitsky cells and are not related to smoking. As these tumours can be asymptomatic or present with nonspecific symptoms, a high index of suspicion is essential to make an early diagnosis which determines the prognosis. Surgery is curative and remains the mainstay of treatment. Case presentation: A 41-year-old female with no background medical illness first presented with a spontaneous left sided pneumothorax requiring a chest tube insertion. High-resolution CT (HRCT) thorax detected an incidental solitary pulmonary nodule. Bronchoscopy revealed a smooth round tumour sitting at the ostium of the basal right lower lobe bronchus. Endobronchial biopsy was complicated with massive bleeding requiring emergency exploration via rigid bronchoscopy. Multiple attempts to secure haemostasis using Watanabe spigot and argon plasma coagulation failed. She was intubated with a double lumen tube to isolate the healthy left lung. An urgent CT pulmonary angiogram (CTA) was performed to look for collaterals and feasibility of embolization, but no collaterals were seen. She was then referred to the cardiothoracic surgeon for an emergency right lobectomy. Histopathological examination revealed typical carcinoid tumour. She was discharged from the hospital in a stable condition. Discussion: Bronchial carcinoids embryologically originate from the foregut and patients rarely present with features suggestive of carcinoid syndrome and crisis. Mostly are asymptomatic resulting in late presentation and diagnosis. Majority of the typical carcinoids are centrally located and may present with obstructive symptoms and recurrent pneumonia. Bronchoscopists may face massive bleeding following endobronchial biopsy in bronchial carcinoids. Conclusion: Massive bleeding after endobronchial biopsy can occur and therefore the bronchoscopist should have anaesthesia, interventional radiology, and cardiothoracic support to handle this complication. Using tumour markers may obviate the need for biopsy in typical bronchial carcinoids to prevent massive bleeding after endobronchial biopsy.